Один вариант уравнений устойчивости оболочек слоистой структуры с межфазными дефектами - Верещака, Сергей Михайлович (НТУ "ХПИ", 2006)
On the basis of the discrete-structural theory of thin shells the variant of the equations of stability of settlement model of multy-layer thin-walled elements with several rigid anisotropic layers is offered. It is considered, that the pressure of cross shift and pressure on border of contact are equal among themselves. It is supposed elastic slipping on a surface of contact of adjacent layers. The permitting equations of stability are received with the account of nonlinear deformations and deformations of cross shift and pressure
Keywords: оболочки из композитов; деформирование; уравнение Рейснера; уравнения равновесия